ENGINEERING TEACHER'S PEDAGOGICAL MASTERY: WAYS TO IMPROVE - F. T. Shageeva (Высшее образование в России, 2017)
This paper has been written within the framework of a discussion regarding the status of engineering pedagogy, as well as its definition and typology. While solving the problem of the unity and polarity of roles played by a faculty member at an engineering university, such as teacher, researcher, or resource specialist, some questions arise, such as: how can all these teacher's functions be balanced? How can we ensure the efficiency of teaching activity without loss of its integrity? Contemplation will inevitably lead to the problem of teacher's pedagogical mastery and the necessity of searching for the ways to improve and develop it. The paper discusses the essence and structure of pedagogical mastery and the ways to form and improve it. This question is very important for engineering university teaching staff, which, as a rule, have no basic psychological and pedagogical education. The author dwells on the advanced training program developed at the Chair of Engineering pedagogy of Kazan National Research Technical University. The program consists of several modules aimed at the improving engineering teacher's pedagogical mastery.